Isopropyl(ene)-type Cembrane Diterpene an Important Chemotaxonomical Marker in Bornean Soft Coral Genus Sarcophyton - Phan, Chin Soon; Charles Santhanaraju Vairappan (2015)
Two cembrane diterpenoids; (+)-11,12-epoxysarcophytol A (1) and sarcophytol W (2) were isolated from Sarcophyton sp. collected from Mantanani Island, Sabah. Secondary metabolites structures were elucidated based on spectroscopic data. This is the first record of cembranoid diterpenes isolated from the Bornean soft coral genus Sarcophyton. The isopropyl(ene)-type cembrane derivatives could be suggested as chemotaxonomical markers for soft coral genus Sarcophyton.